Efektifitas Pelatihan Penatalaksanaan Kecemasan Pada Siswa Kelas 9 SMP Salman Al-Farisi Bandung - Ardena Maulidia Hamdani; Gilang Yubiliana; Andri Abdurrochman; Risti Saptarini (Universitas Hasanuddin, 2020)
The study was conducted to determine the effectiveness of anxiety management training as a preventive measure to minimize the negative effects of anxiety before facing the national exam in grade 9 students of SMP Salman Alfairisi Bandung. Data collection was carried out using questions related to the material presented during the training. This research method is quasi-experimental in the form of one group pre-test, post-test design. The training was conducted for one day with 80 students as research subjects. Participants were measured during the pre-test, then given treatment in the form of training and given a post-test. The material provided is about 1) Understanding anxiety and causative factors; (2) The symptoms of anxiety and the effects of anxiety; and (3) coping anxiety; and (4) simulation by doing roleplay due to anxiety and relaxation techniques. The post-test is calculated with the difference in the mean value. The analysis was performed using paired sample ttest with a significance value of 0.000 <alpha (0.05). The results of this study indicate that training in anxiety management in grade 9 students is effective. Participants can understand the material presented properly based on an increase in scores during the post-test.